From commodity booms to economic miracles: Why Southeast Asian industry lagged behind - Jean-Pascal Bassino; Jeffrey G. Williamson (University of the Philippines, School of Economics (UPSE), 2015)
Except for the Philippines between 1896 and 1939, Southeast Asia was never part of the century-long East Asian industrial catching up until after World War II. Before the 1950s, Southeast Asian manufacturing hardly grew at all: while commodity export processing did grow fast, import-competing manufacturing and manufacturing for local consumption did not. Singapore and Thailand started recording catching up growth rates on the western leaders only from the 1950s onwards, and Indonesia and Malaysia joined the club only after 1973. Even then, Southeast Asia did not record catching up growth rates on Japan or Taiwan until after 1973 and 1990, respectively. The only Southeast Asian country that appeared to have joined the fast industrial growth club before World War II - the Philippines - had its industrial growth collapse after the ISI years. What explains this dismal industrial performance before the 1960s? Why did Southeast Asia become a rapid export-led manufacturing growth success story after the 1960s while it did not in Latin America, the Middle East, or South Asia? In seeking answers, we distinguish four periods: de-industrialization and commodity export growth before 1913; a modest diversification into manufacturing during WWI and the interwar years; the development of consumer goods production under import substitution policies between the 1940s and the 1960s; and finally the high speed export-led industrialization since. We show how factor endowments, demography, schooling, second-best institutions, foreign markets, and, especially, good luck mattered.
Keywords: F14; L60; N65; O14; 330; Manufacturing growth; Southeast Asia; history